Pengaruh Software GeoGebra dalam Pembelajaran Discovery Learning Terhadap Hasil Belajar Peserta didik Kelas X SMAN 1 Padangan - Ardhani, Defi Kurnia; Manoy, Janet Trineke (MATHEdunesa, 2025)
To find out how much GeoGebra influences the effectiveness of learning and helps students overcome the challenges of learning with technology, it is necessary to conduct research on its impact on learning outcomes in discovery learning. The purpose of this study is to determine whether students of class X SMAN 1 Padangan who use GeoGebra-assisted discovery learning and students who do not use GeoGebra have significantly different learning outcomes. This study used a quasi-experimental approach with non-equivalent control groups. The 72 students in the study were divided into two groups: the experimental group, which used GeoGebra as an aid, and the control group, which did not use Geogebra. Tests, which included pretests and posttests, were used to collect data. After the exams were administered, SPSS was used to process and evaluate the students' test results. The findings demonstrated that there was a significant difference in learning outcomes between the experimental and control classes, with the posttest hypothesis test's significance value being 0.001 < 0.05. Next, based on the N-Gain test, the average N-Gain percentage for the experimental class was 66%, classified as moderately effective. In contrast, the control class achieved an average N-Gain percentage of 48%, categorized as less effective. This indicates that the discovery learning model supported by GeoGebra has a positive impact and is more effective in enhancing mathematics learning outcomes on quadratic function topics.